2021
DOI: 10.1111/jcal.12549
|View full text |Cite
|
Sign up to set email alerts
|

Teacher‐created video instruction in the elementary classroom—Its impact on students and teachers

Abstract: Despite the proliferation of multimedia devices in elementary classrooms, there is limited research examining teacher‐created video instruction, particularly regarding its effect on academic growth and engagement. This study investigated the effect of teacher‐created computer‐based video instruction (CBVI) using iPads on students' academic, behavioural and affective learning in elementary classrooms. The study used a repeated‐measures design with counterbalancing to measure the effects of CBVI during mathemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Also, the majority of students had a negative attitude towards using third-party videos. Torrington & Bower (2021), who compared the effect of students' instructor voice and a stranger's voice on cognitive load and achievement, found that a stranger's voice increased students' cognitive load and decreased success, although it was not statistically significant. Also, most of the students stated that their instructor's voice helped them to stay focused.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the majority of students had a negative attitude towards using third-party videos. Torrington & Bower (2021), who compared the effect of students' instructor voice and a stranger's voice on cognitive load and achievement, found that a stranger's voice increased students' cognitive load and decreased success, although it was not statistically significant. Also, most of the students stated that their instructor's voice helped them to stay focused.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, SMGE's topical topics in recent years were not found relevant to the emergence of new technology but rather the COVID-19 pandemic. Research contents revolved around improving the quality of online teaching in the context of the pandemic, such as curriculum, [85] assessment, [86,87] teacher professional development, [87,88] improving classroom teaching, [89] teaching and learning strategies, [90,91] cooperative and collaborative learning, [92] mobile learning, [90] human-computer interface. [92] Last, it is noted that this study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Aligned with Torrington and Bower (2021), teacher videos positively impact both elementary school students and teachers in learning. This study also identified best practices for how teachers in environments with limited access to technology and facilities constantly develop themselves with ideas, creativity, and innovation.…”
Section: Discussionmentioning
confidence: 99%